A nonrandom association of breast implants and the formation of desmoid tumors. Issue 10 (27th August 2021) - Costa, Philippos Apolinario; Marbin, Staci; Costa, Bruna Menon Loureiro Apolinario; Espejo‐Freire, Andrea Patricia; Saul, Eduardo Edelman; Barreto‐Coelho, Priscila; Allen, Ahkeel; Hakim, Muhammad O.; Goel, Neha; D'Amato, Gina Z.; Subhawong, Ty; Trent, Jonathan C.
Abstract: Background: Studies suggest that surgical breast augmentation with implants is a risk factor for breast desmoid tumors. The statistical strength of this correlation is unknown, as evidence is limited to anecdotal reports. Methods: Patients with breast desmoid tumors and a history of breast implants seen at a single center between 2000 and 2021 were identified via radiology, breast, and sarcoma databases. The standardized incidence ratio (SIR) was calculated to assess the correlation between breast desmoid tumors and breast implants. The cases were pooled with published cases for analyses. Progression‐free survival curves and hazard ratios were estimated using the Kaplan‐Meier method and Cox proportional‐hazards modeling. Results: Fourteen patients from one institution and 66 cases in the literature were identified. All patients were female, and the mean age was 38 years old (range 20–66). 63 patients (82%) underwent resection, 9 (12%) received chemotherapy, 3 (4%) received sorafenib, 11 (14%) received hormonal therapy, and 3 (4%) underwent active surveillance. After resection, the 2‐year recurrence‐free survival rate was 77% (95% CI 65%–89%). The recurrence risk was lower for resection with no residual tumor (R0) compared to microscopic (R1) or macroscopic (R2) residual tumor (HR: 0.15; 95% CI 0.02–0.8; p < 0.05). The SIR was 482 (95% CI 259–775) to 823 (95% CI 442–1322), suggesting a 482–823 times higher risk of developing a breast desmoid tumor after breast augmentation than the general population. Conclusion: We present a nonrandom association between breast implants and desmoid tumors. Whether the tumors arise from the surgical trauma or the implant's biomaterial is unknown. When surgery is indicated, negative margins reduce the risk of recurrence.